2009
DOI: 10.1177/0149206308329967
|View full text |Cite
|
Sign up to set email alerts
|

Board Characteristics, Managerial Incentives, and the Choice Between Foreign Acquisitions and International Joint Ventures

Abstract: Drawing on the agency theory, corporate governance, and international business literatures, the authors link board characteristics and managerial incentives to the choice between acquisitions and joint ventures by firms entering foreign markets. Hypothesized relationships are examined in the context of 383 acquisition and 171 joint venture entries undertaken by relatively nondiversified firms in the U.S. manufacturing sector during the period 1991 to 1999. Findings indicate that firms with boards characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 140 publications
0
64
0
2
Order By: Relevance
“…Similarly, Lien et al [2005], aft er having analysed over 200 publicly listed companies in Taiwan, concluded that there is only limited statistical support for the impact of board characteristics upon the decision to undertake FDI. Datta et al [2009] used a dataset consisting of close to 400 acquisitions and 200 joint ventures, in the US manufacturing sector. Th eir fi ndings indicate that fi rms with boards characterised by a higher proportion of outside directors, independent leadership structures and fi rms with a separation of the Chief Executive Offi cer (CEO) and board chair positions are more inclined to favour acquisitions over joint ventures, in their foreign market entry.…”
Section: Th E Study Accomplishments and The Research Objectivementioning
confidence: 99%
“…Similarly, Lien et al [2005], aft er having analysed over 200 publicly listed companies in Taiwan, concluded that there is only limited statistical support for the impact of board characteristics upon the decision to undertake FDI. Datta et al [2009] used a dataset consisting of close to 400 acquisitions and 200 joint ventures, in the US manufacturing sector. Th eir fi ndings indicate that fi rms with boards characterised by a higher proportion of outside directors, independent leadership structures and fi rms with a separation of the Chief Executive Offi cer (CEO) and board chair positions are more inclined to favour acquisitions over joint ventures, in their foreign market entry.…”
Section: Th E Study Accomplishments and The Research Objectivementioning
confidence: 99%
“…Accordingly, we construct the measure of CEO tenure as the number of years during which the current CEO served in this role in a given firm (e.g., Westphal and Zajac, 1995). CEO/Chairman separation is coded as a dummy variable, taking the value of 1 if the CEO and chairman roles are separated, and 0 if both roles are performed by the same individual (e.g., Datta, Musteen and Herrmann, 2009). CEO ownership is operationalised as the value of equity held by the CEO in absolute values.…”
Section: Control Variablesmentioning
confidence: 99%
“…Differences in national culture, customer preferences, business practices, and institutional forces increase transaction costs when conducting investment abroad [12,19,20]. Furthermore, information asymmetry in foreign markets requires great efforts from executives to adjust to local market conditions, posting significant challenges in achieving strategic objectives [21,22].…”
Section: Challenges Of Fdismentioning
confidence: 99%
“…In particular, although joint ventures (JVs) and acquisitions (ACs) are both characterized by the involvement of an ex-anti target/partner selection, negotiation process, and ex-post integration efforts, the two modes face challenges that are qualitatively different. Contrary to the partial equity investment as found in JVs, the full-investment of capital in ACs involves in-depth resource commitment, which causes investing firms to be more vulnerable to environmental uncertainty, thereby leading to higher venture risk [20,25]. Further, ACs assume full control, and thus require greater efforts from investing firms to overcome integration challenges, such as how to harmonize culture conflicts between acquiring and target firms, reconcile discrepancy of organizational systems, and prevent turnover of acquired human capital [24].…”
Section: Specific Learning From Director Fdi Experience Within Focal mentioning
confidence: 99%
See 1 more Smart Citation